HONORIFIK BAHASA JEPANG (KEIGO) DALAM SURAT ELEKTRONIK DI PERUSAHAAN JEPANG - Mutiara Ayu Surya; Rina Marnita; Fajri Usman (Center of Language and Cultural Studies, 2022)
This research is aimed to describing the honorific terms and their relationship with the users’ social status. This study focuses on the use of Japanese honorific forms used on emails by the employees in a Japanese company. The method of this research is qualitative-based procedure consisting the techniques of collecting data and the steps of analyzing data. The data are collected from the emails sent and received by Japanese employers and employees in the company confidentially. The relationships between the forms and the social status of the users are identified based on Harada’s theory. As a result, this research proves that the honorific address term sama is used to address socially lower receiver than the sender. Other forms of honorifics found in this study are the performative honorific. It is the dominant type of honorific on the emails. This honorific is used to address the receiver with higher and lower social status than the sender. This research shows that the social status in a working environment is not an absolute factor in the use of honorifics.